Robust microhoneycomb-like nanofibrous aerogels derived from cellulose and lignin as highly efficient, low-resistant and anti-clogging air filters - Ma, Daphne Xiu Yun (2022)
In this article, we report highly porous yet robust microhoneycomb-like nanofibrous aerogels (NFAs) with porous cell walls and hierarchical porous structures, and their potential as durable high-performance air filters. The NFAs are fabricated from cellulose nanofibers and kraft lignin via directional ice-templating and low-temperature annealing. We found that lignin could effectively boost cross-linking reactions during the annealing, greatly enhancing the mechanical robustness of the NFAs. It also effectively minimizes annealing-induced shrinkage of the NFAs, avoiding significant porosity and pore-size reduction. Our filtration test results reveal that these robust NFA filters exhibit excellent filtration performance for particles over a wide range of sizes, including 0.1 μm and most penetrating particles. In particular, a high filtration efficiency of 99.86% with a fairly low pressure drop (ΔP) of 59.5 Pa could be achieved for 0.1 μm particles at the face velocity of ∼5 cm s−1, for which the corresponding quality factor (QF) is significantly higher than that of reported aerogel air filters fabricated using predominantly natural materials. The outstanding QF achieved could be attributed to the preferably aligned pores and porous cell walls that help to ease the airflow and create longer and tortuous travelling paths for diffusive particles while within the pores the loose, tangled nanofibers with surface functional groups could facilitate particle deposition. Moreover, heavy loading filtration tests show good long-term filtration efficiency and anti-clogging features of the NFAs. Overall, this work provides a new strategy to prepare durable NFA air filters that are capable of mitigating the tradeoff between the filtration efficiency and ΔP, and alleviating the potential microplastic pollution caused by the disposal of petroleum-based plastic filters into environments.